Parental leave and beyond : recent international developments, current issues and future directions - Moss, Peter, 1945-; Duvander, Ann-Zofie E.; Koslowski, Alison Smith, 1975- (Policy Press, 2019)
This volume provides an international perspective on parental leave policies in different countries, goes beyond this to examine a range of issues in depth, and aims to stimulate thinking about possible futures and how policy might underpin them.